THE IMPORTANCE OF TECHNOLOGICAL MEANS IN THE MODERN EDUCATION SYSTEM (Conferencea, 2022)
The evidence in this paper shows that technology has a positive effect on student learning expectations and outcomes. Evidence also shows that technology integration is becoming more common in public and private schools. Technology integration is shown to be effective in all age groups and is also shown to be helpful for students with special learning needs.